Increased attentional load moves the left to the right. Issue 2 (7th February 2016) - Bonato, Mario; Cutini, Simone
ABSTRACT: Introduction: Unilateral brain damage can heterogeneously alter spatial processing. Very often brain-lesioned patients fail to report (neglect) items appearing within the contralesional space. Much less often patients mislocalize items' spatial position. We investigated whether a top-down attentional load manipulation (dual-tasking), known to result in contralesional omissions even in apparently unimpaired cases, might also induce spatial mislocalizations. Method: Nine right-hemisphere-damaged patients performed three computer-based tasks encompassing different levels of attentional load. The side of appearance of visual targets had to be reported either in isolation or while processing additional information (visual or auditory dual task). Spatial mislocalizations (from the contralesional hemispace towards the ipsilesional unaffected one) were then contrasted with omissions both within and across tasks, at individual as well as at group level. Results: The representation of ipsilesional targets was accurate and not affected by dual-tasking requirements. Contralesional targets were instead often omitted and, under dual-task conditions, also mislocalized by four patients. Three cases reported a significant number of left targets as appearing on the right (alloesthesia). Two of these patients perceived more targets (albeit to a wrong spatial location) under dual- than under single-task load. In a fourth patient, increased visual load resulted in synchiria, the (mis)perception of single, contralesional targets as being two (one on each side). Conclusions: When the neural circuitry subtending spatial processing is damaged, an increase in task load can lead to either a disregard or a bias in the processing of contralesional hemispace. The spatial bias subtending mislocalizations seems to index a more severe deficit than neglect, as if contralesional space would be completely erased rather than merely ignored.